2021
DOI: 10.3390/plants10081694
|View full text |Cite
|
Sign up to set email alerts
|

LEA13 and LEA30 Are Involved in Tolerance to Water Stress and Stomata Density in Arabidopsis thaliana

Abstract: Late embryogenesis abundant (LEA) proteins are a large protein family that mainly function in protecting cells from abiotic stress, but these proteins are also involved in regulating plant growth and development. In this study, we performed a functional analysis of LEA13 and LEA30 from Arabidopsis thaliana. The results showed that the expression of both genes increased when plants were subjected to drought-stressed conditions. The insertional lines lea13 and lea30 were identified for each gene, and both had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Additionally, an increasing number of studies have found that LEA may be involved in more regulatory mechanisms. For example, the mutant of AtLEA13 and AtAtLEA30 were found to be more sensitive to drought stress due to their increased transpiration and increased stomatal density [45]. The overexpression of the OsLEA1a gene in rice could protect plants from various abiotic stresses by preventing cell membrane damage and increasing the plant's ability to scavenge reactive oxygen species [37].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an increasing number of studies have found that LEA may be involved in more regulatory mechanisms. For example, the mutant of AtLEA13 and AtAtLEA30 were found to be more sensitive to drought stress due to their increased transpiration and increased stomatal density [45]. The overexpression of the OsLEA1a gene in rice could protect plants from various abiotic stresses by preventing cell membrane damage and increasing the plant's ability to scavenge reactive oxygen species [37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another factor influencing stomatal density is the level of certain protein groups in the late stages of embryogenesis (LEA). López-Cordova et al (2021) explained that LEA (Late Embryogenesis Abundant) protein is involved in the tolerance mechanism against drought stress and stomatal density. The result of this study found that both cowpea and long bean plants had a similar response by reducing the number of stomata (stomatal density) and the width of the stomatal opening under drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Late embryogenesis abundant (LEA) proteins are a large protein family that mainly functions in protecting cells from abiotic stress; however, these proteins are also involved in drought tolerance and the determination of stomatal patterning and density. The overexpression of LEA13 and LEA30 , CaLEA6 and CaLEA73 (from Capsicum annuum ), and MsLEA4-4 (from Medicago sativa ) genes in Arabidopsis thaliana plants increased drought tolerance due to lower transpiration and stomatal density compared to control plants [ 82 ]. Homeodomain leucine zipper (HD-Zip) transcription factors are plant-specific TFs that participate in abiotic stress responses, and MdHB7-like (an HD-Zip I TF) was identified as a drought-induced gene in apple plants.…”
Section: Molecular Regulation Of Stomatal Density For Osmotic Stress ...mentioning
confidence: 99%